Settler-colonialism's "miscarriage":thinking the failure of relationality through Irigaray's "Interval" - Faulkner, Joanne (Angelaki, 2019)
The relation between Australia’s First Nations peoples and settler-colonial Australians may be characterised as having “miscarried” to the extent that colonial difference is unacknowledged, and Aboriginal peoples are expected to assimilate to white Australian culture. This paper brings Luce Irigaray’s feminist thought into dialogue with Indigenous philosophy and activism to think through this “relation” – or absence of relation. For Irigaray the miscarriage of relationality takes place between women and men when the sexual relation is mischaracterised as procreation, and thus reified as the concrete “child,” rather than conceived as a living, changing “interval” that is shared and maintained by each. Likewise, while coloniser Australians have – via appropriation of Aboriginal children – reduced the relation with Aboriginal peoples to one of absorption or assimilation, First Nations political action offers something akin to Irigaray’s “interval”: a third term co-produced by two different parties, through which they might negotiate equally the terms of their togetherness and autonomy. By creatively reworking Western conventions and concepts, Aboriginal activists and artists invite the coloniser to share a future grounded in acknowledgement of First Nations sovereignty and lore, whilst also challenging the authority of those Western conventions and concepts. As a case in point, I propose that, while the “interval” may certainly help forge a relation between two thought traditions, Aboriginal activism exposes the limitations of Irigaray’s philosophy with regard to thinking cultural difference, marked, as it is, by an absence of serious engagement with other traditions and perspectives.